A comparison of the Nickel and the conventional geothermometers with respect to the Jagersfontein and the Matsoku kimberlite peridotite xenolits - Mofokeng, Sipho Wiseman (Department of Geological Sciences, 2014)
Bibliography: leaves 116-125.